Unpredictable stress in adolescnt mice: long-term effects on neurochemistry and on behavior - Lima, Ana Paula; Reis-Silva, Thiago Marinho; Sandini, Thaísa Meira; Massoco, Cristina (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2016)
Adolescence is one of the most critical period of development and has a great importance to the health of an adult life. Stressors or traumatic events during this period are associated with changes in the development and plasticity of the neuroendocrine system predisposing the individual to psychiatric disorders as related to anxiety or depression. However stress in adolescence is a very discussed topic and there are few studies about the longterm effects of stress during this period. Therefore, this study aims to assess the impacts in adulthood of unpredictable stress during adolescence on behavioral tests